2005
DOI: 10.1093/brain/awh679
|View full text |Cite
|
Sign up to set email alerts
|

Distinct right frontal lobe activation in language processing following left hemisphere injury

Abstract: Right hemisphere activation during functional imaging studies of language has frequently been reported following left hemisphere injury. Few studies have anatomically characterized the specific right hemisphere structures engaged. We used functional MRI (fMRI) with verbal fluency tasks in 12 right-handed patients with left temporal lobe epilepsy (LTLE) and 12 right-handed healthy controls to localize language-related activity in the right inferior frontal gyrus (RIFG). During the phonemic task, LTLE patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
2
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(77 citation statements)
references
References 58 publications
4
68
2
3
Order By: Relevance
“…These were the conclusions of a PET study, which found bilateral activation in anterior insulae elicited by sentence stimuli (Wong et al, 2002). Right hemisphere frontal areas offer resources to maintain language function and this points to the high likelihood of a pre-existing language network in the right hemisphere that can be recruited when needed (Perani et al, 2003;Voets et al, 2006;Winhuisen et al, 2005). For example, a number of reports indicate that language dominance shifts to homologous righthemisphere regions following a disabling left hemisphere brain injury (Lazar et al, 2000;Staudt et al, 2002;Tivarus et al, 2012).…”
Section: Receptive and Expressive Languagementioning
confidence: 80%
“…These were the conclusions of a PET study, which found bilateral activation in anterior insulae elicited by sentence stimuli (Wong et al, 2002). Right hemisphere frontal areas offer resources to maintain language function and this points to the high likelihood of a pre-existing language network in the right hemisphere that can be recruited when needed (Perani et al, 2003;Voets et al, 2006;Winhuisen et al, 2005). For example, a number of reports indicate that language dominance shifts to homologous righthemisphere regions following a disabling left hemisphere brain injury (Lazar et al, 2000;Staudt et al, 2002;Tivarus et al, 2012).…”
Section: Receptive and Expressive Languagementioning
confidence: 80%
“…Althought it is diffi cult to distinguish between neuropathological changes and normal language development (Yuan et al 2006), it is largely accepted that the age is the primary factor for predicting recovery with prognosis so far better in children under age of six. Thus, under the age of six, the language plasticity is refl ected by supplementary involvement of the homologue hemisphere and decrease of the degree of specialization (Muller et al 1999a;Brazdil et al 2003;Liegeois et al 2004;Demonet et al 2005;Pataraia et al 2005;Thivard et al 2005;Helmstaedter et al 2006;Voets et al 2006;Yuan et al 2006). Is is also refl ected by intra-hemispheric reorganization of cerebral networks (Lazar et al 1997;Bell et al 2002;Pataraia et al 2004), meaning that regions not originally involved in a specifi c language operation, become involved after reorganization.…”
Section: Age Of Seizures Onsetmentioning
confidence: 99%
“…The onset of seizures before age of six (Goldmann and Golby 2005;Yuan et al 2006) and originated in the left predominant hemisphere could induce either inter-hemispheric (bilateral or right hemispheric) (Liegeois et al 2004;Muller et al 1999aMuller et al , 1999bVoets et al 2006) or intra-hemispheric (Bell et al 2002;Pataraia et al 2004) reorganization of language. Overall, it is generally accepted that the right shift of language tends to be stronger and concerns more numerous language regions in patients with early seizures, as compared to patients with late (after age of six) lesions (Muller et al 1999a).…”
Section: Introductionmentioning
confidence: 99%
“…Language functions are likely to become reorganized in patients with slow growing tumors including low grade gliomas 11,17) as well as congenital anomalies in the left hemisphere. 2,16) In our case, the lesion probably had a long growth interval, allowing the language areas to shift into the intact area in the ITC. However, we cannot prove this speculation due to lack of information about the language areas in the early stage of the present case.…”
Section: Discussionmentioning
confidence: 60%